1986
DOI: 10.1111/j.1365-2265.1986.tb03621.x
|View full text |Cite
|
Sign up to set email alerts
|

Response to Neurotransmitter Modulating Drugs in Patients With Cushing's Disease

Abstract: We designed a systematic study of patients with Cushing's disease to compare the results of acute experiments with cyproheptadine, sodium valproate and bromocriptine with the results of chronic treatment with sodium valproate. In 13 patients the plasma cortisol response to single doses of 2.5 mg bromocriptine, 6 mg cyproheptadine and 300 mg sodium valproate was assessed over 4-8 h. All patients were then treated with sodium valproate 200 mg three times a day for a period of 3 months. Subjects were classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…Valproate blocks GABA reuptake enhancing GABA inhibition of hypothalamic CRH release. Clinical reports of valproate-responsive patients with CD have emerged (Cavagnini et al 1984, Koppeschaar et al 1986, Colao et al 1997. However, chronic administration and placebo-controlled studies failed to confirm the ACTHlowering effects of valproate , Colao et al 1997.…”
Section: Valproic Acid (Valproate)mentioning
confidence: 99%
“…Valproate blocks GABA reuptake enhancing GABA inhibition of hypothalamic CRH release. Clinical reports of valproate-responsive patients with CD have emerged (Cavagnini et al 1984, Koppeschaar et al 1986, Colao et al 1997. However, chronic administration and placebo-controlled studies failed to confirm the ACTHlowering effects of valproate , Colao et al 1997.…”
Section: Valproic Acid (Valproate)mentioning
confidence: 99%
“…[3]. However, clinical remission in Cushing's disease induced by sodium valproate has been reported occasionally [4,10,11] but these cases appear to be very rare. These inconsistend results may be explained by the fact that in Cushing's disease the underlying dis order appears to be heterogenous.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years sodium valproate, an anticonvulsant, has been shown to decrease plasma ACTH levels in Nelson's syndrome [5,6,9]. However, the efficacy of sodium valproate Abbreviations: ACTH = Adrenocorticotrophic hormone; CRF = Corticotropin releasing factor in pituitary dependent Cushing's syndrome remains controversial [1,3,4,6,10,11,13]. This study evaluates the effectiveness of sodium valproate in different ACTH hypersecreting states and investigates the site of its action.…”
mentioning
confidence: 99%
“…However, trials in series of consecutive patients revealed that only fewer than 25% of unselected patients respond to bromocriptine. A clinical response to low-dose (less than 10 mg) bromocriptine in 15 cases has been reported thus far (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), while tumor shrinkage has been reported in only 3 cases (9,16,18) (Table 2).…”
Section: T a B L E 2 Re P O R T E D Ca S E S O F Cu S H I N G ' S Dmentioning
confidence: 97%